Uganda’s agrifood system structure and drivers of transformation - Diao, Xinshen; Ellis, Mia; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2023)
Uganda experienced annual economic growth of 5.8 percent between 2009 and 2019 (UBOS 2020). While restrictive COVID-19 policy measures in 2020 and 2021 caused a slowdown in the economy, the country has largely been spared the adverse effects of the global commodity market disruptions arising from the Russia-Ukraine war that started in 2022 and from the 2023 global recession (Arndt et al. 2023; Diao and Thurlow 2023). Uganda’s GDP growth is projected to reach 5.5 percent in 2023 and 6.1 percent in 2024 (World Bank 2023), suggesting that the economy is resuming its pre-pandemic growth trajectory. Agriculture remains an important sector, accounting for one-quarter of GDP and two-thirds of Uganda’s jobs. The agriculture sector also performed well in the 2009 to 2019 period, growing at 5.0 percent annually (UBOS 2020). Thanks to a positive terms of trade shock and an established trade surplus in agrifood products, this sector played an important role in weathering the 2022 and 2023 global commodity market shocks (Diao and Thurlow 2023). In this brief, we examine Uganda’s economic growth and transformation trajectory, both historically and going forward. Rather than focusing on the role of primary agriculture, we examine how the country’s broader agrifood system (AFS) is contributing to that transformation process.